Hyperspectral FTIR imaging of irradiated carbonaceous meteorites. (1st September 2018) - Brunetto, R.; Lantz, C.; Dionnet, Z.; Borondics, F.; Aléon-Toppani, A.; Baklouti, D.; Barucci, M.A.; Binzel, R.P.; Djouadi, Z.; Kitazato, K.; Pilorget, C.
Abstract: Space weathering produces variations in the optical properties of small solar system body surfaces. Laboratory studies have been performed by several groups on different meteorite classes, aimed at simulating space weathering by using ion irradiation and laser ablation. Here we present new FTIR spectral imaging data of ion irradiated carbonaceous chondrites (CV Allende and CM Murchison meteorites), simulating solar wind irradiation on primitive asteroids. Irradiation conditions (40 keV He + and Ar + up to 3.10 16 ion/cm 2 ) were reported in detail in previous studies. The new analyses were performed with a FTIR micro-spectrometer equipped with an FPA (Focal Plane Array) detector. Micro-reflectance spectra were acquired in the 2.5–12 μm range using a spot size of 20 μm and scanning large areas (from mm 2 to cm 2 ) of the meteorite pellets, both on virgin areas and on areas irradiated with different doses. Spectral maps allow us characterizing the heterogeneity of the meteorites at the 20 μm spatial scale. In the irradiated areas, we observe spectral modifications of both anhydrous and hydrated silicates. Spectral shifts are observed after irradiation, larger for anhydrous than hydrated silicates. Compositional heterogeneity of the pristine materials and irradiation effects are compared to each other as a function of the irradiation dose, to determine which spectral features are more sensitive to space weathering. Results are then compared with the IR spectral capabilities of instruments onboard the Hayabusa2/JAXA and OSIRIS-REx/NASA spacecrafts, to provide these missions with spectral criteria on how to distinguish space weathering from compositional heterogeneity effects at the asteroid, and in view of surface selection for sample return. Highlights: We irradiate carbonaceous meteorites with 40 keV ions simulating asteroid weathering. We perform FTIR micro-spectral imaging on areas irradiated with different doses. Irradiated anhydrous and hydrated silicates peak positions show spectral redshifts. We separate compositional heterogeneity of pristine materials and irradiation effects. We discuss implications for Hayabusa-2 and OSIRIS-REx sample return missions.